Self Development of Novice Teacher of English: Challenges and Opportunities - Fenisya Anggraini (Jurnal Bahasa dan Sastra, 2019)
Abstract: To compete in the 21st century, it is very important for novice teachers to have self- development in developing their professional development. Lack of experiences in teaching and adapting in a new environment makes them know the ways to face the challenges and the opportunities to support their future carrier. Self development is taking steps to be better in your- self such as by learning new skills or overcoming bad habits. It takes bigger portion than other aspects in developing their professional development. This paper highlights self-development as one of the components in developing the professional development of the teachers. This covers the challenges of self development, coping with the challenges and opportunities of developing self development.Keywords: Self development, novice teachers and professional developmentAbstrak: Agar dapat bersaing dalam abad ke-21, sangat penting bagi guru pemula untuk memiliki pengembangan diri dalam mengembangkan profesionalnya. Kurangnya pengalaman dalam mengajar dan beradaptasi di lingkungan baru membuat guru tahu cara menghadapi tantangan dan peluang untuk mendukung karier masa depan. Pengembangan diri berarti mengambil langkah- langkah untuk menjadikan kualitas diri lebih baik seperti dengan mempelajari keterampilan baru atau mengatasi kebiasaan buruk. Dibutuhkan porsi yang lebih besar daripada aspek lain bagi guru pemula dalam mengembangkan pengembangan profesional. Makalah ini akan menyoroti pengembangan diri sebagai salah satu komponen dalam mengembangkan profesional para guru. Ini mencakup tantangan pengembangan diri, mengatasi tantangan dan mengembangkan kemampuan diri.Kata-kata kunci: Pengembangan diri, guru baru dan pengembangan profesional